THE EFFECTIVENESS OF EDUCATION IN INCREASING HYPERTENSION KNOWLEDGE IN HYPERTENSION PATIENTS AT THE PRATAMA CLINIC UIN SUNAN AMPEL SURABAYA - Asiyah, Siti Nur; Rizqiah, Dhuhrotul; Retnaninggalih, Anjani Putri; Suyatno, Restiani L.; Winarto, Agnestria; Zahroh, Aini Nurul Fatimatuz; Najjah, Alisa Hidayatun; Syaroh, Roza Maulida Muhanna; Purwati, Nur Fatihah (HEARTY, 2024)
Hypertension is a condition where the systolic blood pressure is 130 mmHg or diastolic is 80 mmHg; 80 – 95% in cases of essential hypertension. Hypertension can also be called the "silent killer" because hypertension does not show real symptoms, but can lead to life-threatening complications such as coronary heart disease, stroke, kidney failure and heart failure. Hypertension is also the biggest cause of the percentage of the population who have health complaints or disease morbidity in the world. Hypertension sufferers are estimated to reach 1.5 billion in 2025 and deaths can reach 9.4 million individuals. The purpose of this study was to determine the effectiveness of education in increasing knowledge of hypertension in patients with hypertension at the Pratama Clinic of Sunan Ampel State Islamic University (UINSA) Surabaya. The population in this study were patients with hypertension at the Primary Clinic UINSA Surabaya as many as 14 people. This study uses a quantitative method with One-Group Pretest-Posttest Design. The results of the study using the Mc Nemar statistical test obtained a value of = 0.031 <0.05. That is, providing education is effective in increasing knowledge of hypertension in hypertension patients at the UINSA Primary Clinic Surabaya.